Uji Sitotoksik Ekstrak Daun Andrographis paniculata Ness. pada Kultur Limfosit T Pasien Systemic Lupus Erythematosus - Febriandaru, Dedi; Febrinasari, Ratih Puspita; Febrinasari, Ratih Puspita; Wijayanti, Lilik; Wijayanti, Lilik (Nexus Biomedika, 2013)
Background: Systemic Lupus Erythematosus or SLE is a chronic autoimmune disease with varied clinical manifestations. SLE prevalence in Indonesia is being dominated with female, especially in their productive age. Certain etiology of SLE is still unknown until now, but genetic factors and immune system are being estimated as the primary factors. The first line therapy of SLE is cyclophosphamide. Unfortunately if being consumed more than six months, cyclophosphamide has several side effects, like bone marrow depression, infections, alopecia, hemorrhagic cystitis, and infertility. Because of that side effects, herbal medicine is being developed nowday. One of them is Andrographis paniculata Ness. leaf. The aim of this study was quantitative cytotoxic test for Andrographis paniculata Ness. leaf on T lymphocyte culture of Systemic Lupus Erythematosus. Methods: This study was anexperimental study. Subjects in this study were patients with SLE who appropriated SLEâs criterias and normal people without allergy and autoimmune diseasesâs history. This study was done by doing T lymphocyte culture from intravenousâs blood sample and observing cellâs absorbance with ELISA reader. Collected data were used for determining live cellâs percentage (IC50) and analyzed with Statistical Product and Service Solution (SPSS) 11.00 for Windows. Mean resistance data was tested by linear regression test. Results:The result showed that IC50 dose of Andrographis paniculata Ness. leaf extract treatment on SLE samples was smaller than the normal people. In Andrographis paniculata Ness. leafâs extract treatment, IC50 in SLE = 0.00074 and in normal people = 0.19584. Conclusion: Andrographis paniculata Ness.leaf extract had stronger cytotoxic effect on T lymphocyte culture of patients with SLE than the normal people. Keywords: Systemic lupus erythematosus, Andrographis paniculata Ness. leaf extract, T lymphocytes, IC50